Application of three water quality indices in a tropical river of Costa Rica: the case of the Durazno River (UNED Research Journal, 2025)
Introduction: In Costa Rica, surface waters face increasing threats due to urban expansion, livestock farming, and inadequate wastewater treatment. The Durazno River micro-watershed is a representative example of areas with mixed land uses, making it an ideal model studying water quality. Few studies in Costa Rica compare multiple indices simultaneously, particularly those incorporating emerging contaminants. Objective: To comparatively evaluate the water quality with three indices: Canadian Council of Ministers of the Environment Water Quality Index, National Sanitation Foundation Water Quality Index, and Dutch Classification System. Methods: From 2022–2024, We conducted four sampling campaigns per year at upper, middle, and lower river sites, analyzing 14 physicochemical and microbiological parameters including nutrients, DO, pH, fecal coliforms, and emerging contaminants (cefotaxime and doxycycline). We applied Generalized Linear Models with Box-Cox transformation to evaluate effects of location, season, and year. Results: The Canadian index was the most sensitive, rating water quality marginal to poor and detecting clear spatial and seasonal differences; the National Sanitation Foundation Water Quality Index showed uniformly medium quality with low spatial variation, while the Dutch index indicated consistently low contamination due to its limited parameter set. There were year-to-year differences (likely tied to rainfall-driven changes in suspended solids and nitrates) and emerging contaminants peaked near livestock/urban zones, confirming anthropogenic impact. Conclusion: Water quality in the micro-basin according to the three indices ranged from normal to poor. The three indices provided complementary perspectives, but the Canadian index had greater diagnostic capacity by incorporating a broader set of parameters. Using multiple indices improves water quality assessment accuracy and decision-making, revealing priority intervention zones, especially when emerging contaminants are integrated into national monitoring programs.
Keywords: emerging contaminants; environmental monitoring; multivariable analysis; water resource management; water quality indices; urban basin; anthropogenic impact